STRATEGIES FOR THE INTERNATIONALIZATION OF COMPANIES IN PANDEMIC TIMES - Pereira, Maria Eduarda Araujo; Azevedo, Gabriel Maranho; Fumagalli, Luis André Wernecke (Caderno PAIC, 2022)
After the Covid-19 outbreak, which had its origins back in late 2019, companies underwent many changes in how they operated and kept their business running. Specifically, the way these companies are using to start a process of internationalization or to keep their business in other countries is also changed, to keep in sync with how the world was changing throughout the pandemic. This paper aims to analyze and comprehend which strategies companies adopted to keep internationalizing their operations. To reach this goal, exploratory and qualitative research was adopted with bibliographic and documentary research to obtain the data and information. Based on this exploration, it was possible to state that the international market has gone through many transformations just as companies that underwent the process of internationalization during the pandemic. It was also possible to conclude that this process of internationalization was restructured, and different strategies had to and have to be used nowadays.